The use of misoprostol for cervical priming prior to hysteroscopy: a systematic review and analysis - Hua Y; Zhang W; Hu X; Yang A; Zhu X (Dove Medical Press, 2016)
Ying Hua, Wenwen Zhang, Xiaoli Hu, Ansu Yang, Xueqiong Zhu Department of Obstetrics and Gynecology, The Second Affiliated Hospital of Wenzhou Medical University, Wenzhou, People’s Republic of China Abstract: The effects of misoprostol use on cervical priming prior to hysteroscopy have been controversial. Therefore, a systematic literature review and meta-analysis of studies were conducted to assess the effect of misoprostol on cervical priming prior to hysteroscopy. All studies published before July 2014 with data related to the use of misoprostol for cervical priming compared with placebo or no medication prior to hysteroscopy, were identified. Twenty-five randomized controlled trials involving 2,203 females were systematically analyzed. The results showed that, compared with placebo or no medication, the use of misoprostol prior to hysteroscopy led to a significant relief of the need for cervical dilatation, resulted in a significantly greater cervical width, had fewer hysteroscopy complications, and mild and insignificant side effects. Subgroup analyses revealed that the regimen of 200 or 400 µg vaginal misoprostol may be a simple and effective method for cervical priming, especially prior to operative hysteroscopy. Keywords: misoprostol, hysteroscopy, cervical priming, cervical dilatation, complications, systematic review